Educação e robótica educacional na escola pública: as artes do fazer - Barbosa, Fernando da Costa (2011)
In this investigation we analyze a group work with Educational Robotics held daily in a public school elementary schools in Uberlândia, Minas Gerais, that for three semesters, studied involved teachers at the Federal University of Uberlandia, students of Mathematics and Computer Science Graduate Program in Education, teachers and students of the Municipal. The production of this investigation focused on systematic analysis of a set of data on activities of students at ninth year of elementary school, and this analysis consists of three elements: the organization of collective work, the interaction between the subjects of work, scenarios developed and designed with the digital education educational Robotics. The data were produced by means of observations of classes in the school computer lab and records in audio, video and writing of Field Notes; also we analyzed production of blogs, videos and robots using information and communication activities with educational robotics free and Lego robotics kits. We also take into account the student responses to a questionnaire prepared and their testimonies collected in interviews. This research showed that the collective work realized has overcome some obstacles to some problems concerning the physical and financial structure of the School and the University. Overcome this situation, after all, confirmed to us that every school needs the space and materials activities, which requires investment and financial costs to build, equip, and keep running educational institutions throughout the school years. Also allowed us to build roads to a digital education in the context of public education using educational Robotics. In terms of digital education was possible to present and teach students to make a conscious use of the Internet and encourage the development of blogs as a space for authorship and reflection. In the process of education was possible to establish methodologies for working with different media allowing an advance in the development of robotics activities. The integration of media helped in the interaction of students in activities and on building relationships primarily with the mathematical knowledge of construction and robotics projects conceived and worked at the school.